2007
DOI: 10.1016/j.juro.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laparoscopic and Open Radical Cystoprostatectomy for Localized Bladder Cancer With 3-Year Oncological Followup: A Single Surgeon Experience

Abstract: The laparoscopic approach provides the benefit of lesser blood loss and postoperative pain in patients undergoing radical cystectomy for organ confined bladder cancer. The oncological outcome is comparable to that of open radical cystectomy at 3-year followup. However, longer followup in a larger cohort of patients is needed to assess long-term oncological and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 16 publications
8
68
1
4
Order By: Relevance
“…Other encouraging results were recently published by Snow-Lisy et al [8] in a cohort with the currently longest follow-up after minimally invasive RC, they reported OS and CSS rates of 48% and 71% at 5-years, and 35% and 63% at 10-years, compatible with our present findings. Furthermore, our present survival rates appear consistent with other mid-term reports after minimally invasive RC [27][28][29][30]. In particular Mmeje et al [30], in 50 patients with LN-positive disease after RARC, reported OS rates at 3 and 5 years of 55% and 45%, respectively.…”
Section: Long-term Oncological Outcome Of Lrcsupporting
confidence: 92%
See 1 more Smart Citation
“…Other encouraging results were recently published by Snow-Lisy et al [8] in a cohort with the currently longest follow-up after minimally invasive RC, they reported OS and CSS rates of 48% and 71% at 5-years, and 35% and 63% at 10-years, compatible with our present findings. Furthermore, our present survival rates appear consistent with other mid-term reports after minimally invasive RC [27][28][29][30]. In particular Mmeje et al [30], in 50 patients with LN-positive disease after RARC, reported OS rates at 3 and 5 years of 55% and 45%, respectively.…”
Section: Long-term Oncological Outcome Of Lrcsupporting
confidence: 92%
“…which probably accounts for their lower RFS rate. Our present results are also [8,9,27]. Huang et al [9] in 171 patients undergoing LRC in China reported a 5-year RFS rate of 72.6%.…”
Section: Long-term Oncological Outcome Of Lrcsupporting
confidence: 79%
“…Through different types of urinary diversion, the feasibility and safety of laparoscopic RC (LRC) has been demonstrated by several urologists (6 -8). However, LRC is associated with prolonged operative time and the real advantage of LRC over open RC (ORC) is not yet known because the data on comparison of LRC with ORC on a prospective basis are not sufficient-only two comparative studies published to date (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the oncological and perioperative outcomes of the largest LRC series is presented in Table 2 [30,[32][33][34][35][36][37][38][39][40][41], with that of ORC from recognized centres of excellence [1,2,[4][5][6]21]. These LRC series are based on relatively few patients with a shortterm follow-up, and are representative of the early experience.…”
Section: Lrc: Initial Resultsmentioning
confidence: 99%